2007
DOI: 10.1016/j.jacc.2007.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Myeloperoxidase Predict Mortality After Myocardial Infarction

Abstract: Myeloperoxidase and protein carbonyl levels are elevated in plasma after acute MI, apparently via independent mechanisms. High MPO is a risk factor for long-term mortality and adds prognostic value to LVEF and plasma NT-proBNP measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(200 citation statements)
references
References 42 publications
(45 reference statements)
9
187
0
4
Order By: Relevance
“…Although ELISA is easy to use, only few reports have compared the various kits to determine their accuracy and reliability. Comparisons of in-house MPO ELISA with commercial kits generally show strong positive correlations (Pearson correlation coefficient >0.9) [120,121]. However, there is concern around the accuracy of the assays given that different concentrations of MPO can be obtained in the same samples when applying different ELISA kits/methods [120].…”
Section: Detection Of Mpo Proteinmentioning
confidence: 99%
“…Although ELISA is easy to use, only few reports have compared the various kits to determine their accuracy and reliability. Comparisons of in-house MPO ELISA with commercial kits generally show strong positive correlations (Pearson correlation coefficient >0.9) [120,121]. However, there is concern around the accuracy of the assays given that different concentrations of MPO can be obtained in the same samples when applying different ELISA kits/methods [120].…”
Section: Detection Of Mpo Proteinmentioning
confidence: 99%
“…In addition, serum MPO levels are elevated in human stroke patients compared with normal subjects (12) and can predict future stroke and vasculopathic events in Fabry disease (13). Additionally, serum MPO levels are elevated in other cardiovascular diseases in humans, including myocardial infarction (14), congestive heart failure (15), and peripheral vascular disease (16). Therefore, whereas inflammation is a complex cascade of events involving different types of cells and molecules, MPO could be used as a biomarker for inflammation, and a noninvasive method to identify MPO activity in the ischemic brain could allow clinicians to identify those patients that would most likely benefit from antiinflammatory therapy.…”
mentioning
confidence: 99%
“…Similar findings were observed by Esporcatte et al 16 in a heterogeneous group of chest pain patients. Mocatta et al 17 showed a significant relationship between abovemedian levels of MPO after acute myocardial infarction and increased 5 y mortality. Nonetheless, we were unable to show an association of MPO with cardiovascular events in long-term follow-up.…”
Section: Discussionmentioning
confidence: 97%